Nurse’s identity role during Covid-19: Perception of the professional identity of nurses during the first wave of infections of the Covid-19 pandemic - Rossi, Sandra; Cosentino, Chiara; Bettinaglio, Gloria Caterina; Giovanelli, Franca; Prandi, Carmen; Pedrotti, Paolo; Preda , Davide; D'Ercole, Alfonso; Sarli, Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. The main purpose of the study is to investigate the experience of nurses who worked in the Covid-19 area focusing on the perception of their role. In particular, has been explored the nurses’ perception of job satisfaction in relation to the images sent back by public opinion through the mass media and social communication channels. During the first wave of Covid-19 nurses have acquired media visibility , but their feeling is represented more by the discomfort of finding themselves suddenly glorified in the face of a lack of professional, social, and economic recognition. Materials and methods. A Mix-Method methodology and convenience sampling was adopted, on the population of professionals and students in post-graduate specializations, belonging to the Department of Medicine and Surgery of the University of Parma, and by nurses from the ASST-Bergamo Asst Bergamo Est, Lombardia Italy, who worked in the Covid emergency during the first wave of the pandemic, from February 2020 to May 2020. In the quantitative phase Stamm’s Professional Quality of Life Scale - ProQOL was administered to 89 respondents through a Google Form, In the qualitative phase, 3 Focus Groups were conducted on a total of 17 students . Results. At the ProQol questionnaire, a moderate score was found in the Compassion Satisfaction scale (CF = 38.28) and in the Secondary Traumatic Stress subscale (STS-24.33), while low values emerged in the Burnout subscale (BO = 16.02). From the focus groups emerged five specific thematic: Professional collaboration, Job satisfaction, Nurse’s personal skills, Failure to protect the public image and the nursing profession. Conclusions. The professional collaboration, union with the work team, sense of solidarity, job satisfaction, professional growth and awareness of one’s role seem to have worked favorably on Compassion Satisfaction, while keeping Compassion Fatigue levels under control.